Debut. Russian for beginners - Snegurova, T.; Romanov, Yu.; Paramonova, V. (NTU "KhPI", 2016)
The guide includes a range of material to give students the essential skills and knowledge they need for basic Russian reading, speaking, and writing (up to A2 Council of Europe language descriptor). This course is intended for a very wide audience of Russian language learners, pursuing various goals (living and studying in those countries where Russian is spoken; short-term Russian courses; traineeship; language credits, etc.).

Посібник містить матеріали, що мають на меті формування у студентів базових знань і навичок російського читання, говоріння та письма (до рівня А2 за мовним дескриптором Ради Європи). Посібник призначено для широкого кола студентів, які вивчають російську мову для різних цілей (проживання та навчання в країнах, де говорять російською; короткострокові курси російської мови, стажування, отримання академічних кредитів з іноземної мови і т.д.).
Дебют. Русский язык для начинающих
Keywords: russian as a foreign language; L2 teaching; L2 learning; interlanguage; подготовительный факультет; студенты-иностранцы; обучение иностранных студентов; русский язык; уровень А2